How multi-lane, one-way street design shapes neighbourhood life: collisions, crime and community. Issue 8 (3rd August 2017) - Riggs, William; Gilderbloom, John I. "Hans"
ABSTRACT: Global recognition of the need for more liveable and "complete" streets has allowed for increased funding to bicycle and pedestrian projects. That said, many streets in urban neighbourhoods remain unsafe. This study hypothesises that some of these issues related to safety issues are tied to multi-lane, one-way streets, which exist primarily in urban business districts and historic neighbourhoods, often occupied by poor and minority residents. There has been little research in this area to test how one-way street configurations relate to collisions, crime and community. To examine this, we use three principal strategies: (1) a cross-sectional citywide evaluation using descriptive and inferential statistics on all collisions occurring within a five-year period in a mid-sized city; (2) a focused assessment of traffic collision data, crime data, counts of trees, housing valuation data, foreclosure and vacant and abandoned structures on a 13-block street segment with both one- and two-way streets and (3) a qualitative broken windows assessment, using photography to evaluate signs of visual distress on one-way versus two-way segments. Our results show a higher incidence of collisions and injuries on multi-lane streets than on their two-way counterparts – for motorists, bikes and pedestrians. Our photographic assessment suggests that these street typologies contribute to degradation and erosion of community. Our results show that neighbourhoods with one-way multi-lane streets experience greater abandonment, lower housing values and slower increases in property values. This research supports expanded thinking about one- to two-way street conversion as a method to improve safety, connectivity, community and sustainability.